An update to remedial avenues for complaints about poor care in the NHS. Issue 4 (2nd April 2021) - Sonar, Ulhas; Eevuri, Maheswara Reddy; Kolpattil, Sangeetha; Kumar, Shyam
Abstract : As an institution, the NHS is liable to respond and act on any concerns or complaints against the services it provides. NHS organisations should provide Patient Advice and Liaison Services as a first point of contact for patients, carers and/or relatives. Complaints raised by patients or their representatives should be investigated in an open, evidence-based way, aiming to resolve the issue to the fullest satisfaction of the complainant within an agreed time frame, while maintaining strict confidentiality. Complainants should be safeguarded and supported with appropriate advice. If a satisfactory resolution is not provided within 6 months, the complainant has the right to escalate the issue to the Parliamentary and Health Service Ombudsman. With this in mind, the aim of this article is to provide an overview for NHS staff regarding the avenues available for complainants.